Applicant reaction to structure : self-monitoring as a moderator - Alias, Alizi (2010)
This experimental study examined applicant reaction on different types of interview structure (through structured, semi-structured and unstructured interview transcripts) with further analysis of self-monitoring as moderator variable. Final year undergraduate students (n=41) were selected and imagined themselves as applicant applying for the post of research assistant (RA). The results showed a significant effect of interview structure on applicants‟ reactions with F (1, 40) =35.29; p<0.01. Particularly, applicants reacted negatively to structured interview compared to semi-structured (t(41) =-8.67; p<0.01) and unstructured interview (t(41) =-5.94; p<0.01). No significant difference was found in applicants‟ reactions between semi-structured and unstructured interview with t(41) =1.56; p>0.05 and self-monitoring did not moderate effect of interview structure on applicant reactions with F(2, 38) = 2.626, p>0.05; η²=0.121.